2006
DOI: 10.1080/13576500500294620
|View full text |Cite
|
Sign up to set email alerts
|

Do left-handed children have advantages regarding school performance and leadership skills?

Abstract: A handedness polymorphism exists in all human populations so far investigated, at least since the Palaeolithic. Handedness is a heritable trait, and a possible evolutionary explanation for the higher prevalence of right-handers is the association of left-handedness with some deleterious traits. In this context, the persistence of left-handers remains unexplained. Reproductive success has been shown to be dependent on cultural success in many human societies. This study is the first attempt to consider the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 54 publications
1
24
1
4
Order By: Relevance
“…Post Campus, 720 Northern Boulevard, Brookville, NY 11548, USA. e-mail: joseph.piro@liu.edu J. Piro & C. Ortiz study (Faurie, Vianey-Liaud, & Raymond, 2006;Sommer, Aleman, Somers, Boks, & Kahn, 2008;Thilers, MacDonald, & Herlitz, 2007). We also sought to shed light on whether handedness could be associated with domain expertise, as has been proposed in other research, and what this may signal about future expertise in a specific talent domain (Annett & Manning, 1989;Calnan & Richardson, 1976;Casey, Pezaris, & Nuttall, 1992;Crow, Crow, Done, & Leask, 1998;Dellatolas et al, 2003;Martino & Winner, 1995;Min, Shin, & Oh, 1996;Neils & Aram, 1986;Piro, 1993Piro, , 1998Szeszko, Madden, & Piro, 1997).…”
mentioning
confidence: 92%
“…Post Campus, 720 Northern Boulevard, Brookville, NY 11548, USA. e-mail: joseph.piro@liu.edu J. Piro & C. Ortiz study (Faurie, Vianey-Liaud, & Raymond, 2006;Sommer, Aleman, Somers, Boks, & Kahn, 2008;Thilers, MacDonald, & Herlitz, 2007). We also sought to shed light on whether handedness could be associated with domain expertise, as has been proposed in other research, and what this may signal about future expertise in a specific talent domain (Annett & Manning, 1989;Calnan & Richardson, 1976;Casey, Pezaris, & Nuttall, 1992;Crow, Crow, Done, & Leask, 1998;Dellatolas et al, 2003;Martino & Winner, 1995;Min, Shin, & Oh, 1996;Neils & Aram, 1986;Piro, 1993Piro, , 1998Szeszko, Madden, & Piro, 1997).…”
mentioning
confidence: 92%
“…Goldberg et al (1994) find that left-handedness is associated with novelty-seeking, again particularly in males. Looking at several measures of school performance and leadership skills, Faurie et al (2006) find a positive association with left-handedness for boys but a negative one for girls and Sanders et al (1982) find the same pattern for spatial ability.…”
Section: Introductionmentioning
confidence: 99%
“…By extensions, this practice may create an important selective pressure on handedness patterns within given populations (Michel and Harkins, 1985). However, even though studies of manipulative tasks in traditional societies have revealed that some individuals show socially-mediated functional specialization (e.g., Faurie et al, 2005Faurie et al, , 2006, it is commonly assumed that males are more prevalently left-handed. This higher incidence of male lefthandedness in present-day populations has been variously explained as the result of pathology, neurological disorders or trauma (Bakan, 1971;Bishop, 1984).…”
Section: Discussionmentioning
confidence: 97%